2009
DOI: 10.2298/jsc0901053j
|View full text |Cite
|
Sign up to set email alerts
|

Gel-combustion synthesis of CoSb2O6 and its reduction to powdery Sb2Co alloy

Abstract: Sb 2 Co alloy in powdery form was synthesized via reduction with gaseous hydrogen of the oxide CoSb 2 O 6 , obtained by the citrate gel-combustion technique. The precursor was an aqueous solution of antimony nitrate, cobalt nitrate and citric acid. The precursor solution with mole ratio Co(II)/Sb(V) of 1:2 was gelatinized by evaporation of water. The gel was heated in air up to the temperature of self-ignition. The product of gel combustion was a mixture of oxides and it had to be additionally thermally treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Nevertheless, stability studies of such oxide phases under hydrogen and studies about their formation are rare and we have only found two that seems to confirm our reduction stage hypothesis (validated by the H 2 -TPR quantitative analysis). The first reported shows that the oxidation of CoSb 3 leads to a formation of CoSb 2 O 4 , CoSb 2 O 6 , and Sb 2 O 4[65], whereas the second study indicates that CoSb 2 is the final product of the reduction of CoSb 2 O 6 under hydrogen at temperatures ≥ 650 °C[66]. The formation of CoSb 3 can be explained by solid-state reaction (Eq.…”
mentioning
confidence: 99%
“…Nevertheless, stability studies of such oxide phases under hydrogen and studies about their formation are rare and we have only found two that seems to confirm our reduction stage hypothesis (validated by the H 2 -TPR quantitative analysis). The first reported shows that the oxidation of CoSb 3 leads to a formation of CoSb 2 O 4 , CoSb 2 O 6 , and Sb 2 O 4[65], whereas the second study indicates that CoSb 2 is the final product of the reduction of CoSb 2 O 6 under hydrogen at temperatures ≥ 650 °C[66]. The formation of CoSb 3 can be explained by solid-state reaction (Eq.…”
mentioning
confidence: 99%